LEGITIMACY OF THE DISTRICT ATTORNEY FOR THE PROPOSAL OF PUBLIC CIVIL ACTIONS IN THE PROTECTION OF HOMOGENEOUS INDIVIDUAL INTERESTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The complexity of society requires updating the model for processing demands. Even though numerous lawsuits involve a plaintiff demanding the performance of a defendant, there are rights and interests whose ownership is impossible to determine or, when possible, group hundreds or thousands of people. Therefore, there are diffuse, collective rights and homogeneous individual interests. The various norms that regulate the theme list some legitimate assets for the filing of lawsuits, among them the District Attorney. By reading articles 127 and 129 of the Constitution, the legitimacy of the parquet for the defense of diffuse and collective rights remains undisputed. However, there was a stir about the (im)possibility of defending homogeneous individual interests. In this paper, relying on doctrine and jurisprudence on the subject, we seek to answer whether the District Attorney Office can be a legitimate party for the defense in court of homogeneous individual interests and, if so, under what circumstances this will have a legal basis.Keywords: Class actions. District Attorney Office. Homogeneous individual interests.